Detecting stent geometry changes after venous recanalization using duplex ultrasound. (February 2019) - Barbati, Mohammad E; Gombert, Alexander; Toonder, Irwin; van Vuuren, Timme MAJ; Schleimer, Karina; Grommes, Jochen; Wittens, Cees HA; Jalaie, Houman
Background: Patients with post-thrombotic syndrome due to chronic venous obstruction and resistant to conservative management can benefit from endovenous revascularization. The current study investigated the usefulness of duplex ultrasound in monitoring the stent changes over the time. Method: All duplex ultrasound images of treated patients were reviewed retrospectively. The stent diameter and area during the follow-up visits have been analyzed. Result: A total of 210 stents were placed in 137 limbs. Duplex ultrasound findings showed a decrease in area of stent in all patients (mean: 0.69 cm 2 ). Reduction of stent area over the time was a predictor of stent patency (odds ratio: 0.910; confidence interval: 0.832–0.997). Conclusion: Duplex ultrasound has sufficient accuracy in detection of stent changes and its patency. There is a discrepancy between diameter of the stent lumen in vitro and after deployment in all patients. Stent occlusion is related to reduction of stent lumen over the time rather than the percent of the stenosis.